Promotion of breastfeeding: Social mobilization (parade) developed in a health facility in Lima, Peru - Huayhua-Huaraca, Mercedes (2020)
Objective: Evaluate the social mobilization activity called “Breastfeeding Promotion Parade”. Material and Methods: Case study of a social mobilization event (parade) developed by the National Maternal Perinatal Institute of Lima, Peru, between June and August 2019. Participant observation, document review and graphic evaluations of the event were used. The planning: conformation of the executing group, communication system and resources were evaluated. For the execution: the route, the participation in the awareness of pregnant women, family members and the community. For the results, the level of participation of pregnant women, relatives, community, professionals and others were evaluated. Results: For the planning of the event there was a Committee, documentation, phone calls, WhatsApp communication were used, the budget reached $ 900.00. For the execution, the route of the parade was defined. There was adequate participation of pregnant women, family members, community, professionals and others. Conclusion: it was possible to evaluate the social mobilization activity in its main events, planning, execution and evaluation